The Benefits of Learning Management Systems (LMS) in the Effectiveness of Administrative Planning and Learning Implementation - Purwani, Afit Tito (Global Education Journal, 2024)
The development of information and communication technology has brought significant changes to the world of education. One of the most prominent forms of digital transformation is the use of Learning Management System (LMS) platforms, which are systems designed to plan, manage, and evaluate the learning process digitally. This study aims to explain the effectiveness of using a digital learning management system (LMS) platform in facilitating administrative tasks and the implementation of learning processes, particularly at the Sanggar Kegiatan Belajar (SKB) educational institution in East Lampung. A descriptive qualitative approach was used to explore the activities and utilization of the digital learning management system (LMS) platform in facilitating administrative planning and the implementation of learning at the Sanggar Kegiatan Belajar (SKB) educational institution in East Lampung. The research findings indicate that the utilization of the digital learning management system (LMS) platform contributes to the effectiveness of educational administrative planning and the implementation of learning. These findings support the theory that the utilization of digital platforms contributes to more effective educational administrative planning and more engaging learning implementation. The novelty of this study lies in the utilization of digital platforms to enhance the effectiveness of educational administration and the instillation of religious moderation values, thereby making the learning process more effective and enabling the achievement of religious moderation values.